The Diagnostic Process and Multiple Screening Techniques - MURPHY, E. A. (Methods of Information in Medicine, 1972)
Medical examination of the patient may be of two fundamental kinds. It may concern itself with his presenting complaint. It is then a matter of solving a problem by a method which is by nature sequential. It differs logically from classical sequential analysis in that pieces of information to be used as evidence are neither infinite in number nor mutually independent; moreover the process is complicated by considerations of »cost«, by the fact that multiple pieces of information may be solicited simultaneously, and in many cases by the real-time nature of the problem. Alternatively the examination may be directed to the problems of a population as a whole (such as is the case with epidemiological studies, preventive physical examinations and multiphasic screening) where the logical process is more akin to the classical methods for non-sequential analysis. It has not been sufficiently stressed that the clinical introduction of multichannel analysers (which furnish the physician engaged in the first kind of activity with masses of unsolicited information) carries with it the logical attributes of a population study. Two solutions to the consequent logical disruption are suggested: either that the clinician ignore unsolicited information so that the established methods of medicine may be preserved; or that, with respect to unsolicited information the physician assume the responsibilities of preventive medicine with a drastic reorientation of his notions of the normal and the abnormal. The latter course is preferable, but also more complicated. Failure to confront the decision can lead only to chaos.
Keywords: Diagnosis; Screening; Sequential Analysis